Inhibition of USP11 attenuates sepsis-associated acute kidney injury by downregulating TGFBR2/Smad3 signaling - Wang, Lu; Tang, Wen; Jiang, Long; Zhang, Daquan; Wang, Zhigao; Guo, Rennan; Wang, Jingjing; Xiao, Dong (Frontiers in Molecular Biosciences, 2025)
IntroductionSepsis-associated acute kidney injury (AKI) is a common complication of sepsis, which is a severe inflammatory disease with high mortality. The TGF-β/Smad signaling pathway plays an important role in the progression of sepsis, and targeting the TGF-β receptor II (TGFBR2) has been shown to ameliorate its effects. Ubiquitin-specific peptidase 11 (USP11) stabilizes TGFBR2 and enhances the TGF-β/Smad signaling pathway. In this study, we evaluated the effects of USP11 inhibition on sepsis-associated AKI. MethodsA septic mouse model was established and treated with the USP11 inhibitor mitoxantrone. The expression of TGFBR2, phosphorylation of Smad3, as well as the levels of kidney injury markers, inflammatory cytokines, and oxidative stress markers, were measured in kidney tissues. ResultsElevated expressions of TGFBR2 and phosphorylated Smad3 were detected in the kidneys of septic mice, and mitoxantrone treatment was found to reduce the expression of TGFBR2 while suppressing the activation of Smad3. The drug also attenuated kidney injury while reducing inflammation and oxidative stress in the kidneys of septic mice. ConclusionUSP11 inhibition by mitoxantrone ameliorated sepsis-associated AKI by downregulating TGFBR2/Smad3 signaling.